Relation between cerebral activity and force in the motor areas of the human brain. - Dettmers, C; Fink, G; Lemon, R; Stephan, K; Passingham, R; Silbersweig, D; Holmes, A; Ridding, M; Brooks, D; Frackowiak, R (1995)
1. Positron emission tomography (PET) studies were performed in six normal right-handed male volunteers (age 30 +/- 3) to investigate the relationship between cerebral activation as measured by relative regional cerebral blood flow (rCBF) and force peak exerted during right index finger flexion. The purpose was to determine in which central motor structures activity is directly correlated with force for repeatedly executed movements. 2. Twelve PET rCBF measurements were performed in each volunteer with the use of H2(15)O as a perfusion tracer. Volunteers pressed a Morse-key repetitively with their right index finger for 2 min while lying in a supine position in the PET camera. The device was fitted with strain gauges to measure the force peaks exerted upon it. Scans were collected twice each at five different levels of exerted force peak and in a resting state. Individual and group results were co-registered with anatomic magnetic resonance images (MRI). 3. Group analysis revealed four major regions with a high correlation between rCBF and different degrees of repetitively exerted force peaks. One was located in the arm area of the left lateral surface [primary somatosensory and motor cortex (SI, MI)]. The second area was situated on the left mesial surface of the brain, posterior to the anterior commissure (AC) and encompassing the first gyrus dorsal to the cingulate sulcus. This area is thought to be homologous to the posterior part of the supplementary motor area (SMA) in the monkey. The third area was the dorsal bank of the posterior cingulate sulcus. The fourth area showing a significant correlation between rCBF and force peaks was in the cerebellar vermis. 4. Individual PET data were co-registered with each individual's MRI in order to identify precisely the locations of structures demonstrating a positive correlation between rCBF and force peak. Activated areas on the mesial surface consisted of the same two distinct regions seen in the group data. In three subjects the focus on the lateral surface of the cortex appeared to extend into the caudal premotor area; in two it extended into the rostral part of the superior parietal area. In no subject did blood flow in the anterior cingulate areas and anterior SMA show a correlation with the force exerted. Cerebellar correlations were present in the vermis in all subjects.(ABSTRACT TRUNCATED AT 400 WORDS)